Rheology of ice cream: From fundamentals to applications - Pavel Rout; Shreya Saha (Innovations in Agriculture, 2023)
Frozen desserts, including ice cream and related products, have captivated consumer palates for centuries due to their unique combination of taste, texture, and temperature. The complex interplay between ingredients, processing techniques, and the inherent rheological behaviour of these confections has drawn the attention of scientists, engineers, and food technologists alike. Beginning with fundamental insights into the molecular interactions and phase transitions during freezing and storage, the review elucidates the evolving structure-property relationships that define the viscoelastic behaviour of frozen dessert matrices. By dissecting the role of key ingredients, additives, and processing techniques, this article provides a cohesive framework for tailoring the rheological profiles of frozen desserts to achieve desired sensory experiences and stability. Cutting-edge analytical methods, including dynamic mechanical analysis and microstructural imaging, are discussed in the context of their contributions to characterizing and predicting rheological behaviour. The review also highlights practical applications arising from this improved understanding, such as optimized manufacturing processes, enhanced quality control, and the potential to develop novel frozen dessert products with superior texture and flavour delivery. Bridging the gap between scientific insight and industrial practice, this article serves as a valuable resource for researchers, food technologists, and practitioners seeking to advance frozen dessert technology while ensuring product consistency and consumer satisfaction.